Thermodynamic and mechanical stability of Ni3X-type intermetallic compounds. (November 2019) - Kulo, Nada; He, Shuang; Ecker, Werner; Pippan, Reinhard; Antretter, Thomas; Razumovskiy, Vsevolod I.
Abstract: Ni3 X-type intermetallic compounds, also often referred to as γ ′, γ ″, and η precipitates in Ni-base alloys, have been investigated by first-principles methods. Thermodynamic and mechanical stability of Ni3 X (X = Al, Ti, Nb, Mo, Fe, and Cr) compounds has been determined by density functional theory calculations of formation enthalpies and elastic properties of their L12, D022 and D024 phases. In addition, we have investigated the site preference behavior of Al, Ti, Nb, Mo, Fe, and Cr solutes in the L12 -structure Ni3 Al, Ni3 Ti, and Ni3 Nb intermetallic compounds and used this information to investigate the solubility of the aforementioned alloying elements. Our results show that the most stable structures of Ni3 Al, Ni3 Ti, Ni3 Nb, Ni3 Cr, Ni3 Mo, and Ni3 Fe at 0 K are L12, D024, D022, D024, D022, and L12 respectively. Graphical abstract: Image 1 Highlights: The phase stability of Ni3 X (X = Al, Ti, Nb, Mo, Fe, Cr) has been investigated. Ni3 Ti has been identified as the most stable compound. Site occupancy and solubility of solutes in L12 -Ni3 X has been studied.